Joint Position Effects on Biceps Femoris and Peroneal Muscle Activation and Ankle Evertor Strength - Do-eun Lee; Jun-hee Kim; Seung-yoon Han; Oh-yun Kwon (Korean Research Society of Physical Therapy, 2024)
Background: The peroneus longus (PL) and peroneus brevis (PB) function as the primary muscles of eversion, a movement closely associated with tibial external rotation for ankle mor-tise stability. Ankle motion and tibial rotation vary based on different ankle and knee positions. Objects: This study aimed to investigate the PL, PB, and biceps femoris (BF) muscle activation and eversion strength during side-lying isometric eversion exercise based on different ankle positions (neutral [N] and plantarflexion [PF]) and knee positions (90° flexion [KF] and exten-sion [KE]). Methods: Thirty healthy adults with an Ankle Joint Functional Assessment Tool score of ≥ 22 were recruited (mean age = 24.8 ± 3.1 years). Maximal isometric eversion strength and submaximal muscle activation of the PL, PB and BF were measured during isometric eversion exercise in side-lying. A 2 × 2 repeated measures analysis of variance was performed to inves-tigate differences in muscle activation and strength. Results: The PL and PB muscle activation showed significant main effects with the knee and ankle positions (p < 0.05); activation was greater in the KE and PF positions than in the KF and N positions. The BF muscle activation showed a significant interaction effect with knee and ankle positions, which was greater in knee extension and ankle plantarflexed (KEPF) posi-tion than in knee flexion and ankle plantarflexed (KFPF) position (p < 0.05). Eversion strength showed a significant main effect only in ankle position (p < 0.05) and was greater in the N position than in the PF position. Conclusion: The results of this study indicate that the KEPF position can be recommended to facilitate contraction of the PL and PB during side-lying eversion exercise. Furthermore, the effects of the knee-ankle positions should be considered for measuring ankle eversion strength and implementing the isometric submaximal side-lying eversion exercise.